Pengaruh Pengetahuan dan Religiusitas terhadap Minat Mengikuti Asuransi Dana Pendidikan pada Perusahaan Asuransi Syariah - Indah Sari; Nurbaiti Sirait; Nurul Inayah (ManBiz: Journal of Management and Business, 2023)
Education insurance is a type of insurance that provides protection the cost of education to the cost of children's education. The aim of this study to determine the effect of knowledge and religiosity on interest using education fund insurance at sharia insurance companies in the teachers in one of the senior high schools in North Sumatra are partially good or simultaneously. The method used in this research is quantitative method. The population of this study was conducted on teachers in one of the one Senior High School in North Sumatra with a sample of 65 teachers. Using primary data by distributing questionnaires and analytical methods multiple regression using hypothesis testing. The results of this study simultaneously from the variables of knowledge and religiosity have a significant effect on significant to interest. Then partially knowledge variable too has an effect on interest and the variable of religiosity itself also has an effect significantly on the interest in using education fund insurance in Islamic insurance company. Keywords: Knowledge, Reliosity, Interest, Sharia Insurance.